2005
DOI: 10.1197/j.aem.2005.03.004
|View full text |Cite
|
Sign up to set email alerts
|

OPALS Major Trauma Study: Impact of Advanced Life Support on Survival and Morbidity

Abstract: Background:To date, the benefit of prehospital advanced life-support programs on trauma-related mortality and morbidity has not been established Methods:The Ontario Prehospital Advanced Life Support (OPALS) Major Trauma Study was a before-after systemwide controlled clinical trial conducted in 17 cities. We enrolled adult patients who had experienced major trauma in a basic life-support phase and a subsequent advanced life-support phase (during which paramedics were able to perform endotracheal intubation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 13 publications
3
52
0
3
Order By: Relevance
“…First, later year of hospital admission was associated with higher 48-hr mortality. Possible explanations include increasing injury and illness severity over time, evolving clinical care practices (such as more intensive pre-hospital medical care introduced during the study period), 30 or changes in blood product characteristics (such as longer storage time prior to transfusion). We did not consider interactions between illness severity and year of admission in our pre-specified analysis plan, and these associations may not be detected by underpowered statistical tests of interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, later year of hospital admission was associated with higher 48-hr mortality. Possible explanations include increasing injury and illness severity over time, evolving clinical care practices (such as more intensive pre-hospital medical care introduced during the study period), 30 or changes in blood product characteristics (such as longer storage time prior to transfusion). We did not consider interactions between illness severity and year of admission in our pre-specified analysis plan, and these associations may not be detected by underpowered statistical tests of interaction.…”
Section: Discussionmentioning
confidence: 99%
“…It was initiated as a quality improvement project to better understand local blood product utilization, and the results reflect current practice at the time (8-18 years ago). Since this study, pre-hospital trauma care, 30 surgical management of trauma, 54 and intensive care staffing 55 have all evolved, and Canadian physicians have adopted a more conservative approach to red blood cell transfusion in critically ill patients. 56 However, the trend to declining injury-related deaths in Canada during the study period may be due to prevention initiatives rather than to advances in the care of trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…The prehospital world has served as a reminder that during resuscitation, we may have become too intubation focused, at the cost of the physiologic priority of oxygenation. [1][2][3][4] This evidence does not mean that direct laryngoscopy (DL) and intubation were a cause of harm but that physiologic goals must supersede tube placement as a desired end point. Before equating ''A'' with intubation, it is important to consider the following: Is it a ''crash'' situation, where airway control needs to be done immediately?…”
mentioning
confidence: 99%
“…14 Although the benefit of these ALS paramedics was considered dogma for decades and they had become standard in most urban regions in North America, the OPALS studies showed that while some patients benefited from advanced paramedic care, many did not. 15,16 EMS research has greatly expanded in the decade since the OPALS trials were published. Paramedictrained scientists are now working with physicianscientists, EMS operators, governments, and medical directors to conduct research specific to the EMS setting.…”
Section: Ems-centred Researchmentioning
confidence: 99%